Trends in genome diversity of small populations under a conservation program: a case study of two French chicken breeds - Bortoluzzi, Chiara; Restoux, Gwendal; Rouger, Romuald; Desnoues, Benoit; Petitjean, Florence; Bosse, Mirte; Tixier-Boichard, Michèle (Peer Community Journal)

(untitled)
Livestock biodiversity is declining globally at rates unprecedented in human history. Of all avian species, chickens are among the most affected ones because many local breeds have a small effective population size that makes them more susceptible to demographic and genetic stochasticity. The maintenance of genetic diversity and control over genetic drift and inbreeding by conservation programs are fundamental to ensure the long-term survival and adaptive potential of a breed. However, while the benefits of a conservation program are well understood, they are often overlooked. We here used temporal whole-genome sequencing data to assess the effects of a conservation program on the genetic diversity (Δπ), deleterious variation (ΔL), and inbreeding (ΔF) of two local French chicken breeds, the Barbezieux and Gasconne. We showed that when the conservation program is consistent over time and does not undergo any major organisational changes (i.e., Barbezieux), the loss of genetic diversity is limited. This was true for both pedigree and genomic inbreeding but also for the genetic load estimated from functionally important genome-wide variants. However, when a conservation program is interrupted or re-initiated from scratch (i.e., Gasconne), the loss of genetic diversity can hardly be limited as a result of the bottleneck effect associated with the re-sampling. Our results reinforce the imperative to establish and sustain existing conservation programs that aim to keep populations with a relatively small effective population size from the brink of extinction. Moreover, we conclude by encouraging the use of molecular data to more effectively monitor inbreeding at the genome level while improving fitness by tracking protein-coding and non-coding deleterious variants.